2021
DOI: 10.1109/access.2021.3080275
|View full text |Cite
|
Sign up to set email alerts
|

Sim2RealQA: Using Life Simulation to Solve Question Answering Real-World Events

Abstract: As smart speakers continue to proliferate, question answering (QA) by smart devices is being woven into our daily lives. This study assumes question answering related to daily life events detected by context recognition systems, such as activity recognition and indoor positioning systems, e.g., answering questions like "Did my grandma eat dinner?" and "How many times did my grandpa go to the toilet?" These questions can effectively support human memory-aids, locate lost items, and monitor human activities. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Several studies also reported on the improvement of the accuracy of several real-world tasks using data in virtual space. Miyanishi et al [37] proposed an approach for improving the accuracy of real-world question answering tasks using the data obtained from a life simulation game. Hwang et al [38] developed a simulation platform that focused on the daily activities of older adults and used synthetic data to improve the action recognition accuracy.…”
Section: Virtual Space Simulationmentioning
confidence: 99%
“…Several studies also reported on the improvement of the accuracy of several real-world tasks using data in virtual space. Miyanishi et al [37] proposed an approach for improving the accuracy of real-world question answering tasks using the data obtained from a life simulation game. Hwang et al [38] developed a simulation platform that focused on the daily activities of older adults and used synthetic data to improve the action recognition accuracy.…”
Section: Virtual Space Simulationmentioning
confidence: 99%